Merrill General science - David R Kraepel (Charles E. Merril, 1986)
The book provides effective tools for reinforcing the skills that students need to learn science, for teching content visually, for facilitating laboratory activities, for challenging more motivated students, for allowing students to review and condense chapter concepts, and for evaluating student performance. It is organized into sections that follow the text chapters. It also contains an About Activities section provides some helpful tips for conducing the textbook Activities, an overall Program Planning Guide, a section of Basic Skills Masters, and an final section containing Unit Resources and the Final Exam